Drug Transporter‐Mediated Protection of Cancer Stem Cells From Ionophore Antibiotics. (1st July 2015) - Boesch, Maximilian; Zeimet, Alain G.; Rumpold, Holger; Gastl, Guenther; Sopper, Sieghart; Wolf, Dominik
Abstract : Testing of well‐characterized human cancer cell lines was applied to elaborate on whether drug transporters are involved in protection from the cytotoxic effects of the ionophore antibiotics salinomycin and nigericin. The results showed that ionophore antibiotics are less suited to cancer stem cell‐targeted treatment than previously thought. Abstract : Ionophore antibiotics were reported to selectively kill cancer stem cells and to overcome multidrug resistance, but mechanistic studies of the significance of drug transporters for treatment with these compounds are lacking. We applied chemosensitivity testing of well‐characterized human cancer cell lines to elaborate on whether drug transporters are involved in protection from the cytotoxic effects of the ionophore antibiotics salinomycin and nigericin. Our experiments demonstrated that ionophore antibiotics were ineffective against both stem‐like ovarian cancer side population cells (expressing either ABCB1 or ABCG2) and K562/Dox‐H1 cells, which constitute a genetically defined model system for ABCB1 expression. Considering that cancer stem cells often express high levels of drug transporters, we deduced from our results that ionophore antibiotics are less suited to cancer stem cell‐targeted treatment than previously thought. Significance: Ionophore antibiotics such as salinomycin have repeatedly been shown to target cancer stem and progenitor cells from various tumor entities. Meanwhile, cancer stem cell (CSC)‐selective toxicity of ionophore antibiotics seems to be a commonly accepted concept that is about to encourage their clinical testing. This study provides data that challenge the concept of targeted elimination of CSC by ionophore antibiotics. Stem‐like ovarian cancer side population (SP) cells expressing high levels of ABC drug transporters are shown to largely resist the cytotoxic effects of salinomycin and nigericin. Furthermore, using a small interfering RNA‐based knockdown model specific for ABCB1, this study demonstrates that ABC drug transporters are indeed causally involved in mediating protection from ionophore antibiotics. Considering that it is a hallmark of CSCs to exhibit drug resistance conferred by ABC drug transporters, it must be deduced from these results that CSCs may also be protected from ionophore antibiotics by means of drug‐transporter mediated efflux.